Effects of Electroconvulsive Therapy and Repetitive Transcranial Magnetic Stimulation on Serum Brain-Derived Neurotrophic Factor Levels in Patients with Depression - Gedge, Laura; Beaudoin, Ashley; Lazowski, Lauren; du Toit, Regina; Jokic, Ruzica; Milev, Roumen (Frontiers in Psychiatry, 2012)
Objective: Brain-derived neurotrophic factor (BDNF) levels are decreased in individuals with depression and increase following antidepressant treatment. The objective of this study is to compare pre- and post-treatment serum BDNF levels in patients with drug-resistant major depressive disorder (MDD) who received either electroconvulsive therapy (ECT) or repetitive transcranial magnetic stimulation (rTMS). It is hypothesized that non-pharmacological treatments also increase serum BDNF levels. Methods: This was a prospective, single-blind study comparing pre- and post-treatment serum BDNF levels of twenty-nine patients with drug-resistant MDD who received ECT or rTMS treatment. Serum BDNF levels were measured one week prior to and one week after treatment using the sandwich ELISA technique. Depression severity was measured one week before and one week after treatment using the Hamilton Depression Rating Scale. Two-sided normal distribution paired t-test analysis was used to compare pre- and post-treatment BDNF concentration and illness severity. Bivariate correlations using Pearson's coefficient assessed the relationship between post-treatment BDNF levels and post-treatment depression severity. Results: There was no significant difference in serum BDNF levels before and after ECT, although concentrations tended to increase from a baseline mean of 9.95 ng/ml to 12.29 ng/ml after treatment (p= 0.137). Treatment with rTMS did not significantly alter BDNF concentrations (p= 0.282). Depression severity significantly decreased following both ECT (p= 0.003) and rTMS (p< 0.001). Post-treatment BDNF concentration was not significantly correlated with post-treatment depression severity in patients who received either ECT (r= -0.133, p= 0.697) or rTMS (r= 0.374, p= 0.126). Conclusion: This study suggests that ECT and rTMS may not exert their clinical effects by altering serum BDNF levels. Serum BDNF concentration may not be a biomarker of ECT or rTMS treatment response.